The Influence of Organizational Culture on Organizational Performance through Integrated Quality Management in Culinary MSMEs - Ralahallo, Fransiska N; Titioka, Baretha Meisar; Djari, Lukman Hamsah (Green Publisher Indonesia, 2023)
The purpose of this thesis is to advance knowledge about Organizational Culture on Organizational Performance Through Total Quality Management in Culinary MSMEs in Ambon City measured using a Likert scale. A total of 50 respondents were involved in this study using purposive sampling technique. Respondents were selected based on the criteria, namely, the owners of culinary SMEs in the city of Ambon. To test the hypothesis proposed empirically, a hierarchical regression analysis was conducted as a method for analyzing data using XLSTAT PLS PM 2014 software. The results showed that organizational culture had a positive relationship with organizational performance, organizational culture had a positive relationship with total quality management, and quality management integrated has a positive relationship with organizational performance on culinary SMEs in the city of Ambon.